Nanoclay Templated Poly(vinylidene fluoride) Gels - Yadav P.J.P.; Aswal V.K.; Maiti P. (My University, 2025)
Gelation of PVDF has been studies in presence of two-dimensional layered silicate. Nanoclay crystallizes piezoelectric β-phase in gel state as revealed through XRD and electron diffraction studies. Fibrilar morphology of both gel and nanogel is studied through scanning and transmission electron microscopy. The formation of compound of PVDF and solvent is evident while the fraction of PVDF required to form compound is less in nanogel as compared pure gel. The layered structure of assembly in gel and nanogel is revealed through small angle neutron scattering suggesting very small size blob of 7.4 nm for nanogel against the moderately larger size in pure gel of 30.7 nm. Epitaxial crystallization of PVDF in β-phase has been suggested on top of layered silicate. © 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim